2005
DOI: 10.1093/eurheartj/ehi338
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pregnancy in patients after repair of aortic coarctation

Abstract: Pregnancy is well tolerated in women after repair of aortic coarctation. However, an excess of miscarriages and hypertensive disorders of pregnancy were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(81 citation statements)
references
References 27 publications
6
72
2
1
Order By: Relevance
“…Overall, there was an excess of miscarriages and hypertensive disorders of pregnancy. (40) Coarctation is the only CHD known to be an independent predictor of pre-eclampsia.…”
Section: Outcome Of Pregnancy In Left Ventricular Outfl Ow Tract Obstmentioning
confidence: 99%
“…Overall, there was an excess of miscarriages and hypertensive disorders of pregnancy. (40) Coarctation is the only CHD known to be an independent predictor of pre-eclampsia.…”
Section: Outcome Of Pregnancy In Left Ventricular Outfl Ow Tract Obstmentioning
confidence: 99%
“…There is a small risk of aortic dissection in both unoperated and postoperative patients as well as an increased risk of preeclampsia and hypertension. 29,70,71 Using a national database of hospitalizations, a study by Krieger et al 72 demonstrated that women with coarctation of the aorta have a higher risk of hypertensive complications during pregnancy (including preexisting hypertension, pregnancy-induced hypertension, preeclampsia, and eclampsia), a higher risk of adverse cardiovascular outcomes (including heart failure, arrhythmia, stroke, and other embolic events), a higher risk of Caesarean section, increased hospital stays, and higher hospital costs. Aggressive blood pressure control in mothers with unrepaired coarctation may result in decreased uterine blood flow with compromise of fetal growth.…”
Section: Coarctation Of the Aortamentioning
confidence: 99%
“…Aggressive blood pressure control in mothers with unrepaired coarctation may result in decreased uterine blood flow with compromise of fetal growth. 29,70,71 The ESC guidelines suggest an increased risk of aortic rupture and rupture of intracerebral aneurysms in mothers with unrepaired coarctation and in mothers with previous repair who remained hypertensive. 21 Adult patients may have undergone previous intervention with either surgery or catheter intervention.…”
Section: Coarctation Of the Aortamentioning
confidence: 99%
“…By contrast, native coarctation is encountered much less frequently. Pregnancy is usually well tolerated in adequately repaired coarctation [53]. It is essential to assess cardiac status prior to conception, excluding and appropriately managing complications such as recoarctation, aneurysm at the site of repair, an associated bicuspid aortic valve or systemic hypertension.…”
Section: Coarctation Of the Aortamentioning
confidence: 99%